Epic Triumph, Epic Embarrassment, or Both? Commemorations of the War of 1812 Today in the Niagara Region - Forest, Timothy (Ontario History, 2012)
Widely divergent national and local historiographies about the War of 1812 have been created on both sides of the Canadian/American border. This has special significance for the Niagara region, where the two belligerents directly confronted and still confront each other. On the Canadian side of the Niagara River, the Niagara Peninsula has been transformed into a center of regional and national pride. Military leaders, troops and battles are celebrated and events commemorated in a grandiose and triumphant manner. Across the river, Western New York has largely downplayed or outright ignored its role in the very same conflict, to fit in with both the national and local amnesia surrounding the war and the region’s self-conceptualization as a “good neighbour”. This article focuses on public commemorations on both sides of the Niagara to uncover the historical, geographic, economic and demographic explanations as to why the war has been transformed into an epic victory for some, a defeat for others, and an embarrassment best ignored for many.